Activation of Transcription Factor EB Protects Against Proinflammatory Insults Through NF-κB Inhibition in Keratinocytes - Yuqin He; Yanan Sun; Yaojia Cheng; Hui Xing (International Journal of Inflammation Research, 2026)
Keratinocytes are pivotal in mediating cutaneous inflammation. Identifying anti-inflammatory factors within these cells holds promise for developing novel therapeutic strategies to manage skin inflammation. Transcription factor EB (TFEB) has recently emerged as a key regulator linking cellular energy metabolism to inflammatory processes, primarily through its influence on autophagy and NF-κB signaling. However, whether TFEB activation exerts anti-inflammatory effects in keratinocytes remains unclear. In vitro inflammation model was established in HaCat cells by incubation with proinflammatory mediators LPS and IL-1β. Cell viability and TFEB expression and phosphorylation were measured. The effect of TFEB activation by C1 and adenoviral TFEB overexpression on the expression of proinflammatory genes including COX-2, MCP-1 and IL-6 were detected. Also, IκBα protein level were determined. TFEB phosphorylation is increased while TFEB total protein expression is inhibited by treatment with LPS and IL-1β. Pharmacological activation of TFEB by compound C1 and TFEB overexpression suppressed the expression of COX-2, MCP-1 and TNF-α induced by LPS and IL-1β. TFEB overexpression increased basal IκBα expression and restored IκBα level under LPS treatment. TFEB knockdown reduced TFEB expression and lowered basal expression level of COX-2, MCP-1 and TNF-α. Our findings indicate that TFEB activation can mitigate inflammatory gene expression in keratinocytes triggered by LPS and IL-1β. This implicates TFEB as a significant novel modulator of cutaneous inflammation, highlighting its potential as a therapeutic target. Targeting TFEB could thus be a viable strategy for developing new treatments for chronic inflammatory skin conditions.
Keywords: Transcription Factor EB